Investigating Okun’s Law in Nigeria through the Dynamic Model - ADEYEYE, Patrick Olufemi; ODELEYE, Anthonia T.; ALUKO, Olufemi Adewale (Journal of Economics and Behavioral Studies, 2018)
Unemployment is a persistent challenge for countries, especially the developing ones. Nigeria as a developing country faces a herculean task reducing the increasing spate of joblessness amongst her citizens. Okun’s law explains the relationship between unemployment and economic growth in an economy. This study therefore investigates Okun’s law in Nigeria between 1985 and 2015 through the dynamic model. The generalized method of moments estimation result reveals that that present and past output growth are negatively related to unemployment rate. However, only past output growth has a significant effect on unemployment rate. It also shows that past unemployment rate is significantly and positively associated with present unemployment rate. The Toda-Yamamoto Granger non-causality test finds that there is no causality between unemployment and economic growth. This study presents evidence to partially support Okun’s law of inverse relationship between unemployment and output growth and suggests that promoting economic growth can be a policy tool for reducing unemployment rate in Nigeria.